2018
DOI: 10.1016/j.chiabu.2018.03.021
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the mental health impact of childhood abuse and neglect: A replication and extension study in a Brazilian sample of high-risk youth

Abstract: Childhood maltreatment is a key predictor of mental health problems across the life span. Yet, how maltreatment types independently and jointly influence the risk for psychiatric problems remains unclear. The aim of the study was two-fold: first, to replicate recent findings regarding the impact of maltreatment types on youth psychiatric symptoms, based on a Brazilian sample of high-risk adolescents (n = 347; age range = 11-17 yrs), and second, to extend existing findings by examining whether this relationship… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 43 publications
0
17
0
2
Order By: Relevance
“…That evidence complements previous findings from prominent GxE research that placed these maltreatment types among the most relevant exposures for the development of schizophrenia in people with a high load of SZ-PRS [ 11 ]. Emotional abuse was also identified as a particularly strong risk factor for PLE in studies of high-risk populations [ 61 , 62 ]. However, the most plausible explanation for the strong role of emotional abuse (and to lesser extent neglect) may be that these types of CM are the most frequently endorsed and its statistical distribution translates into a higher power.…”
Section: Discussionmentioning
confidence: 99%
“…That evidence complements previous findings from prominent GxE research that placed these maltreatment types among the most relevant exposures for the development of schizophrenia in people with a high load of SZ-PRS [ 11 ]. Emotional abuse was also identified as a particularly strong risk factor for PLE in studies of high-risk populations [ 61 , 62 ]. However, the most plausible explanation for the strong role of emotional abuse (and to lesser extent neglect) may be that these types of CM are the most frequently endorsed and its statistical distribution translates into a higher power.…”
Section: Discussionmentioning
confidence: 99%
“…These findings are in agreement with studies that have evaluated the association between maltreatment and the development of psychopathologies, and the presence of internalizing as well as externalizing symptoms. [16][17][18][19][20][21][37][38][39][40][41][42][43] It should be emphasized that, among the types of maltreatment surveyed, emotional abuse was that most strongly associated with depressive symptoms. This finding is in agreement with previous studies by Bifulco et al, 16 which concluded in favor of a strong association between childhood emotional abuse and development of depression in adulthood, and Cecil et al, 20 which detected greater negative effects on the mental health of victims of emotional abuse.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have demonstrated that experiencing abuse and neglect during childhood increases the likelihood of developing mental disorders in adult life. [16][17][18][19][20][21] Yet, few studies have investigated possible psychological mediators between child maltreatment and mental disorders, 22,23 especially those that could mitigate the negative effects of early experiences of abuse and neglect. 24 Metel et al 22 found that resilience and cognitive biases partially mediate the relationship between early exposure to traumatic life events and depressive symptoms, and recent studies have demonstrated that social support mediates the effect of childhood maltreatment on mental health, [24][25][26][27] but, as far as we know, no studies have investigated LS as a mediator in the relation between childhood maltreatment and mental disorders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Epidemiological studies have consistently shown a high prevalence of mental health problems among children and adolescents in community populations [ 9 ]. The heterogeneity in individual responses to such experiences of maltreatment and emotional abuse is an important predictor of poor mental health throughout life [ 10 , 11 ], and this might lead to the perpetuation of child abuse or neglect between generations. Such intergenerational transmission of maltreatment has been reported based on several theoretical models in Western countries [ 12 – 14 ].…”
Section: Introductionmentioning
confidence: 99%